Growth, mortality and recruitment of commercially important fishes and penaeid shrimps in indonesian waters / A. Dwiponggo, T. Hariati, S. Banon, M. L. Palomares, D. Pauly - Dwiponggo, A. (Filipinas : Research Institute for Marine Fisheries, 1986)
Project background, mateial and methods, results and discussion. Col. Pesc
Table of contents, map, graphs, tables
Keywords: 1. SALTWATER FISH 2. AQUATIC ANIMALS 3. VERTEBRATES 4. GROWTH-MOTALITY-FISH 5. FISHING